FAR AWAY, SO CLOSE...” RISE AND FALL IN THE COAL- MINING BORDER. THE CASE OF CURANILAHUE AND LEBU. 1880- 1930 - Delgado Valdivia, Felipe (Revista de Historia Social y de las Mentalidades, 2012)
The following piece of work deals with  the unequal development registered by  two important coal- mining camps in  the Gulf of Arauco. During this period,  coal industry experiences its greatest  development, which is triggered by  the market growth in our country, the  creation of new routes of transport at an  international level and the beginning of  World War I. Given these circumstances,  Curanilahue becomes the most popular  mining center of its time, with a  great economical power. The railroad  construction which joins this city with  Concepción and Lebu, one of the first  and most traditional coal-mining centers  in Chile, is greatly affected by the 1870  recession, which cannot be defeated in the  future. This crisis reveals signs of decay  and decline that subjugate this place to a  lower position compared to the rest of the  coal- mining centers of that time.
Keywords: Economic History; Regional History; Coal industry; Curanilahue History; Lebu History; XIX century modernization